Cholesterol-lowering drug pitavastatin targets lung cancer and angiogenesis via suppressing prenylation-dependent Ras/Raf/MEK and PI3K/Akt/mTOR signaling. Issue 4 (April 2020) - Hu, Tianjun; Shen, Haibo; Huang, Hongbo; Yang, Zhenhua; Zhou, Yinjie; Zhao, Guofang
Abstract : Therapeutic agents that target both tumor cell and vascular endothelial cell may achieve additional anti-tumor efficacy, particularly in lung cancer due to the critical roles of angiogenesis during lung cancer progression and metastasis. In this work, we showed that pitavastatin, a novel cholesterol-lowering drug, potently inhibited lung cancer cells and angiogenesis. This was achieved by the induction of apoptosis and inhibition of proliferation of lung cancer cells and human lung tumor-associated endothelial cell. Pitavastatin was not only effective to chemo-sensitive but also chemo-resistant lung cancer cells. This was also consistent with the finding that pitavastatin significantly enhanced cisplatin's efficacy in lung cancer xenograft model without causing toxicity in mice. We further showed that pitavastatin inhibited lung tumor angiogenesis in vitro and in vivo through suppressing human lung tumor-associated endothelial cell migration and morphogenesis without affecting adhesion. Mechanistically, we showed that pitavastatin acted on lung cancer cells and human lung tumor-associated endothelial cell through suppressing prenylation-dependent Ras/Raf/MEK and PI3K/Akt/mTOR signaling. Our work is the first to demonstrate the inhibitory effects of pitavastatin on Ras-mediated signaling. Our findings provide pre-clinical evidence to repurpose pitavastatin for the treatment of lung cancer. Abstract : Supplemental Digital Content is available in the text.